Exploring the Efficacy of Inquiry-Based Learning for Human Respiratory System: Students' Achievement at High School Setting - Ramadansur, Rahmat; Sutomo, Edi; Rizky, Ramanda; Sembiring, Al Khudri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
The current research has primary objective that is to assess the effect of implementing the Inquiry-Based Learning Model in enhancing students' academic performance in the field of Science at SMA Smart Indonesia. The Inquiry-Based Learning Model promotes proactive student engagement in exploring, gathering, and interpreting information through independent investigation. The study utilized a quasi-experimental design encompassing pre-test and post-test phases. The participants were selected randomly via a simple random sampling technique. The acquired data underwent analysis using the N-Gain method (T-test). The outcomes revealed a noticeable improvement in the academic performance of students in the experimental group who were exposed to the Inquiry-Based Learning Model, particularly in the context of the human respiratory system. Furthermore, the null hypothesis (H0) was invalidated, as was proven by the 2-tailed Significance value of 0.000 that was smaller than 0.05. This discovery underscores the substantial positive impact of applying the Inquiry-Based Learning Model on enhancing students' academic achievements when compared to conventional teaching methods employed in the control group. In conclusion, this study highlights the significant potential of integrating the Inquiry-Based Learning Model into the Natural Science curriculum at the secondary school level, which could potentially elevate the standard of education and overall student learning accomplishments.